Analisis Jaringan Pipa Transmisi Air Bersih Kecamatan Kandis - Rezky Ardillah; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The need for clean water in Kecamatan Kandis increases with population growth. The community of kecamatan kandis utilizes water source from rain water and Samsam River water. The water obtained will be transmitted to the IPA to be processed into clean water. The minimum plunge of Samsam River was obtained at 217.89 liters / sec. The net water demand after 20 years is 127 liters / sec. In this research, the plan of raw water transmission pipeline system is divided into two networks that will be simulated with EPANET program. Old network along 14674.54 meters and new network along 33708,86 meters by using HDPE pipe. The head and debit values obtained from the simulated results determine which pump to use. This pump is a type of Grundfos type 2 pole pump. This transmission network simulation is expected to be a guide in PDAM planning in Kecamatan Kandis.Keyword: Transmission, clean water, EPANET, HDPE,PDAM.